What is the coverage of your health insurance plan? An audit of hospital billing - Aswin Sugunan; Rajasekharan Pillai K; Anice George (AIMS Public Health, 2024)
The provocative advice of health policymakers in endorsing private health insurance, as a critical tool for health reforms, is well-reckoned as a deterrent to mounting healthcare expenditure in the wake of the public health insurance quagmire. However, scholarly evidence has condemned the ineffectiveness of private health insurance in containing out-of-pocket expenditure. In this backdrop, we carried out a nuanced investigation of the coverage pattern of private health insurance policies. We examined the one-year billing information of private health insurance holders hospitalized in a multi-specialty teaching hospital. We found that private health insurance fails to provide full coverage, leading to underinsurance though minimal financial protection was extended. Moreover, reimbursement patterns under various cost heads are also discussed. We conclude by emphasizing the need for future research to fill the knowledge gap. We claim methodological novelty in its approach to data collection.